Playing with Words and Identity - Notarius, Tania (Vetus Testamentum, 2017)
In this paper I reexamine three expressions in Amos’ visions: לָרִב בָּאֵשׁ (Am 7:4), אֲנָךְ (Am 7:7-8), and קֵץ/קַיץִ (Am 8:1-2). I suggest to understand לָרִב בָּאֵשׁ in Am 7:4 ‘to inundate with fire’ postulating the root ריב ii (parallel to רבב) ‘to bring much water’, etymologically and literarily connecting this expression to the Meribah account. For אֲנךְָ in Am 7:7-8 I substantiate the word-play that incorporates an allusion to 1cs personal pronoun, investigating the involved dialectal Northern Hebrew phenomena in their wider North-West Semitic context: the final vowel reduction in *ˀanāku and the phonetic shifts ō > ū > ī, á > o, and ś > š. For the word-play קֵץ/קַיִץ in Am 8:1-2 I elaborate on its phonetic properties, concentrating on the word-final gemination and the short vowel quality in the lexeme *qiṣṣ. The latter case allows postulating the typological path of the corresponding phonetic development: the diphthong contraction → í > ē in an originally open syllable → í // é allophonism in a double closed syllable → final gemination simplification. As a result, several isoglosses that explicitly separate between Northern and Southern dialects of Hebrew are firmly established: the shorter form of 1cs pronoun ˀanōk vs ˀanōkī and the “Phoenician shift”. The conclusion is that the Northern dialect is close to the Canaanite innovative center, while the Southern dialect represents the conservative periphery.